Gangues da madrugada: práticas culturais e educativas dos pichadores de Fortaleza nas décadas de 1980 e 1990 - Santiago, Naigleison Ferreira (2011)
This present study shows and analyzes certain cultural and educational practices built with gang graffiti movement in Fortaleza city, Ceará, Brazil, in 80’s and 90’s decades. These bold and lawless social people are present and written with a spray and blood, full of vivacity and learning in the city. This research, infected by passion and bias, is against the prejudiced views and moralists who treat these guys as thugs and criminals, who deserve hated purge. With reflections from authors such as Nietzsche and Foucault, about power and pedigree, Maffesoli about hordes and emotional; Certeau, the appropriations, tricks and gimmicks in the city, it´s possible to take a look at this intriguing and challenging movement. Who are these taggers? How do they act? How are cultural and educational practices? What are the conflicts? What are the motivations, even life-threatening, leading the graffiti to mark their features stained glass windows in the city? There are many disturbing questions about this social group that are answered in this experiences and experiences intense study, perceived in many interviews and conversations with those guys, and also support in journals pages that deal constantly writing these taggers write strength in thin walls, bridges, canopies, signs and buildings, considering the city itself as a text, latent and living document of ownership and belonging on part of this social group fully of emotion and action.